Urban Agglomerations and Methods of Delimitation (Zien Journal of Social Sciences and Humanities, 2024)
The article presents the existing approaches to defining the boundaries of urban agglomerations, and the debatable state of this issue is noted. The authors analyzed the current options for the delimitation of urban agglomerations in various countries